Clinker Volume on Seam H’s Distribution and Estimation Based on Coal Mine’s Drill Data - Yoki Dwi Asmoro; Musri Ma'waleda; Sri Widodo (International Journal Labs, 2022)
Clinker is a rock change due to the process of burning and heating coal below the surface. The emergence of well-identified clinkers can prevent loss of coal reserve volume (Loss Reserve) and clinker can be used for haul road surfacing. The purpose of this study is to analyze the distribution pattern of clinker and estimate the volume of clinker through 3D clinker modeling in the H seam of Sambarata Area, Berau Regency, East Kalimantan Province. Research methodology is divided into literature studies, data collection, data processing, data analysis and conclusions. The data used in this study are drill data which include coordinates, elevation, type of lithology, thickness and depth of clinker, and depth of drill points. Data processing and analysis of this study was carried out through clinker correlation using Minescape software version 8.1. Clinker correlation is performed to determine the continuity of the clinker layer from one drill point to another. Based on the results of the analysis on the correlation cross section, it was concluded that the distribution of clinker follows the morphological shape of hills starting from the ground surface at an elevation of +80 to +87 masl to an elevation of +15 to +25 masl horizontally extending towards the North-South according to the direction of the coal seam strike.